Eating pattern and nutritional status of international elite flatwater paddlers - Garcia-Roves, P. M.; Fernandez, S.; Rodriguez, M.; Perez-Landaluce, J.; Patterson, A. M. (International Journal of Sport Nutrition and Exercise Metabolism, 2000)
The aim of this study is to accurately describe the eating pattern and nutritional status of international elite flatwater paddlers during 1 week of a high volume training camp. Ten male and 5 female international elite flatwater paddlers were recruited to take part in this study. These athletes were all members of the Spanish National Team. To assess the intake of energy, macronutrients, and micronutrients, we used the weighed food intake method carried out by an observer. Biochemical and hematological profiles were also obtained. Average daily energy intake in male and female flatwater paddlers was 21.5 ± 2.3 and 16.5 ± 1.7 MJ, respectively. Furthermore, the male athletes showed average carbohydrate and protein intakes of 7.5 ± 0.8 and 2.2 ± 0.3 g á kg-1 body weight á day-1, respectively. Similar intakes were found in female paddlers, carbohydrate 7.3 ± 1.1 and protein 2.0 ± 0.3 g á kgÐ1 body weight á day-1. Daily relative contribution to energy from fat was higher than recommended for sports practitioners or sedentary people (<30 % of daily energy) in both genders (39.1 ± 2.1 and 40.2 ± 2.9% for men and women, respectively). Nevertheless, this diet with a high fat content (rich in monounsaturated fatty acids) did not seem to influence the paddlers' blood lipid profile that presented low values for total cholesterol and tryglicerides and high values for high-density lipoprotein cholesterol (HDL-cholesterol). Flatwater paddlers' micronutrient intake was higher than Recommended Dietary Allowances/Dietary Reference Intake (RDA/DRIs), except for folate that is close to DRI values. Further studies are required in order to understand whether this level of fat intake could impair highly trained athletes' performance and health.